2010
DOI: 10.1007/s10464-010-9338-5
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Student Complaints in the Service Learning Pedagogy

Abstract: This study draws upon student evaluations across 3 years of service learning (SL) courses at a large, urban, faith-based university identifying issues of greatest concern to students. Analysis of qualitative responses revealed perspectives on the limits, pitfalls, and barriers to successful SL student work in the community replicated over the 3 year timeframe. Over 2,200 written responses were coded and tested for reliability for each of 3 years. The top three comments SL students were most likely to express i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 7 publications
(4 reference statements)
0
11
0
Order By: Relevance
“…Whilst previous studies on CBSL have articulated the benefits of the scheme in providing a pedagogical intervention that can support the civic growth of students and provide community outcomes (Binder et al 2015;Bringle and Steinberg 2010;Harkavy and Hartley 2010;Reeb et al 2010), there is very limited research that captures and analyses critical perceptions of the concept. Although Rosing et al (2010) presented some of the criticisms levied against CBSL from the students' perspective; their study did not capture the views of community stakeholders from multifaceted viewpoints. This paper addresses this gap, highlighting the concerns articulated by research participants, and proffers a template for modelling CBSL for student learning and community development.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Whilst previous studies on CBSL have articulated the benefits of the scheme in providing a pedagogical intervention that can support the civic growth of students and provide community outcomes (Binder et al 2015;Bringle and Steinberg 2010;Harkavy and Hartley 2010;Reeb et al 2010), there is very limited research that captures and analyses critical perceptions of the concept. Although Rosing et al (2010) presented some of the criticisms levied against CBSL from the students' perspective; their study did not capture the views of community stakeholders from multifaceted viewpoints. This paper addresses this gap, highlighting the concerns articulated by research participants, and proffers a template for modelling CBSL for student learning and community development.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…'Students have a limited time for their fieldwork. They can only do little within the limited time and should they stay on the field longer than expected, their time will run out against other programmes at the university and the completion of their studies' (Martha,female,(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)Molyko) Similarly, in a study conducted by Rosing et al (2010), it was identified that students were more likely to complain about the scheduling of a CBSL activity. Whilst timing is a recurrent theme in CBSL, it can best be addressed by harmonizing the timescales, operational budgets and requirements of the university, student and internship provider.…”
Section: Participants' Concerns With Cbslmentioning
confidence: 99%
“…Many researchers have asserted that this type of experiential learning should be integrated into nursing curricula (Baker et al, 2004;Bassi, 2011;Downes et al, 2007;Groh, Stallwood, & Daniels, 2011;Laplante, 2009;Peterson & Schaffer, 1999;White et al, 1999;Yeh et al, 2009). In addition, service learning is described as being structured in relation to the service learning placement mission, objectives, preparation, process, site orientation, and task supervision (Downes et al, 2007;Erickson, 2004;Loewenson & Hunt, 2011;Rosing, Reed, Ferrari, & Bothne, 2010).…”
Section: A Structured Form Of Intra-curricular Experiential Learningmentioning
confidence: 99%
“…In CSL, there should be many opportunities to co-learn, co-create knowledge and co-evolve communitybased research theory and practice (Ochocka and Janzen, 2014). CSL requires commitment and resources in order to fulfill both learning objectives and community needs (Rosing et al 2010). The American Association of Community Colleges (AACC) defines CSL as combining community service with academic instruction, focusing on critical, reflective thinking and personal and civic responsibility' (Prentice and Robinson 2010).…”
mentioning
confidence: 99%